Author Correction: CREB-binding protein plays key roles in juvenile hormone action in the red flour beetle, Tribolium Castaneum - Xu, Jingjing; Roy, Amit; Palli, Subba Reddy (Scientific reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.